Control de dolor postquirúrgico en artroplastia total de rodilla en pacientes del Hospital General Regional no. 1, Charo, Michoacán - Rodríguez López, Mariel Adriana (Universidad Michoacana de San Nicolás de Hidalgo, 2023)
Postoperative pain is present in the surgical patient, either due to the disease, the surgical procedure and its complications, or a combination of both. Trauma surgery is considered one of the most painful, its intensity varies from mild to severe, depending on the characteristics of the patient and the procedure performed. This can trigger various complications that delay the recovery of the patient, for this reason, numerous protocols have been proposed for the management of postoperative pain, with the aim of better control, reduction of side effects, less time for the start of ambulation and reduction of rescue analgesic dose requirements. Objective: to describe the different schemes for the control of post-surgical pain, used in patients undergoing total knee arthroplasty, at the Regional General Hospital No. 1 Charo, Michoacán. Material and methods: Observational, descriptive, non-randomized, cross-sectional study, taking as study universe 45 HGR 1 eligible patients, aged 45 to 79 years who underwent total knee arthroplasty. Results: the best control of post-surgical pain was in those patients in whom local anesthetic plus opioid neuraxial anesthesia was performed, with 0% moderate pain for patients in which Morphine was added. The NSAID with the lowest incidence and severity of pain was diclofenac, the addition of dexamethasone demonstrated better pain control. 24.4% of the patients required analgesic rescue, the presence of nausea and/or vomiting, secondary to this, was associated with the administration of opioids. The ambulation began at 15 hours in patients with mild pain and up to 26 hours in patients with moderate pain.

El dolor postoperatorio está presente en el paciente quirúrgico, ya sea debido a la enfermedad, al procedimiento quirúrgico y sus complicaciones o una combinación de ambos. La cirugía traumatológica es considerada de las más dolorosas, su intensidad varía de leve a severa, dependiendo de las características del paciente y del procedimiento realizado. Éste puede desencadenar diversas complicaciones que retrasan la recuperación del paciente, por ello, se han planteado numerosos protocolos para manejo del dolor postoperatorio, con el objetivo de un mejor control, disminución de efectos secundarios, menor tiempo para el inicio de la deambulación y disminución de los requerimientos de dosis analgésica de rescate. Objetivo: describir los diferentes esquemas para el control de dolor postquirúrgico, empleados en los en pacientes sometidos a artroplastia total de rodilla, del Hospital General Regional No. 1 Charo, Michoacán. Material y métodos: estudio observacional, descriptivo, no Aleatorizado, Transversal, tomando como universo de estudio a 45 pacientes derechohabientes del HGR 1, con edad de 45 a 79 años sometidos a artroplastia total de rodilla. Resultados: el mejor control de dolor postquirúrgico fue en aquellos pacientes en los que se realizó anestesia neuroaxial anestésico local más opioide, con 0% de dolor moderado para los pacientes en los que se adicionó Morfina. El AINE con menor incidencia y severidad de dolor fue diclofenaco, la adición de dexametasona demostró un mejor control de dolor. El 24.4% de los pacientes requirieron rescate analgésico, la presencia de náusea y/o vómito, secundaria a éste, se asoció con la administración de opioides. La deambulación tuvo inicio a las 15 hrs en pacientes con dolor leve y hasta 26 hrs en pacientes con dolor moderado.
Facultad de Ciencias Médicas y Biológicas. Instituto Mexicano del Seguro Social. Especialidad en Anestesiología
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/16385; info:eu-repo/classification/cti/3; FCMB-E-2023-0568; Dolor postquirúrgico; Artroplastía total de rodilla; Analgesia postquirúrgica